European Stroke Organisation (ESO) Guidelines for the Management of Spontaneous Intracerebral Hemorrhage. Issue 7 (October 2014) - Steiner, Thorsten; Salman, Rustam Al-Shahi; Beer, Ronnie; Christensen, Hanne; Cordonnier, Charlotte; Csiba, Laszlo; Forsting, Michael; Harnof, Sagi; Klijn, Catharina J. M.; Krieger, Derk; Mendelow, A. David; Molina, Carlos; et al.
Background: Intracerebral hemorrhage (ICH) accounted for 9% to 27% of all strokes worldwide in the last decade, with high early case fatality and poor functional outcome. In view of recent randomized controlled trials (RCTs) of the management of ICH, the European Stroke Organisation (ESO) has updated its evidence-based guidelines for the management of ICH. Method: A multidisciplinary writing committee of 24 researchers from 11 European countries identified 20 questions relating to ICH management and created recommendations based on the evidence in RCTs using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results: We found moderate- to high-quality evidence to support strong recommendations for managing patients with acute ICH on an acute stroke unit, avoiding hemostatic therapy for acute ICH not associated with antithrombotic drug use, avoiding graduated compression stockings, using intermittent pneumatic compression in immobile patients, and using blood pressure lowering for secondary prevention. We found moderate-quality evidence to support weak recommendations for intensive lowering of systolic blood pressure to <140 mmHg within six-hours of ICH onset, early surgery for patients with a Glasgow Coma Scale score 9–12, and avoidance of corticosteroids. Conclusion: These guidelines inform the management of ICH based on evidence for the effects of treatments in RCTs. Outcome after ICH remains poor, prioritizing further RCTs of interventions to improve outcome.